Analysis of pulp histological response to pulpotomy performed with white mineral trioxide aggregate mixed with 2.25% sodium hypochlorite gel in humans: a randomized controlled clinical trial - Karkoutly, Mawia; Alnour, Amirah; Alabdullah, Jamal; Abu Hasna, Amjad [UNESP]; Nam, Ok Hyung; Jalloul, Darin; Al Kurdi, Saleh; Bshara, Nada (Springer Nature, 2024)
This study aimed to evaluate the histological success of pulpotomy in primary molars using white mineral trioxide aggregate (WMTA) mixed with 2.25% sodium hypochlorite (NaOCl) gel and to evaluate in vitro its physical and chemical properties. The study had a clinical stage and an in-vitro stage. The clinical study was conducted with 24 patients aged 8–10 years. It was a randomized controlled trial to perform a histologic evaluation of pulp response following pulpotomy. Primary first molars were randomly assigned in split mouth model to control group—WMTA + distilled water (DW) or experimental group – WMTA + NaOCl gel. Teeth were extracted after 7, 30 or 90 days and submitted to histological analysis. The second stage was an in-vitro study to evaluate the physical and chemical properties of the two materials tested. SEM and EDX analyses and pH level evaluations were performed after 24 h and 28 days. The histological findings revealed that while WMTA + NaOCl gel group showed better odontoblastic integrity (P < 0.05), WMTA + DW group had more favorable outcomes in dentin bridge formation and pulp calcification (P < 0.05). Pulp tissue hemorrhage and pulp fibrosis were similar between them (P > 0.05). Regarding materials’ in vitro evaluation, the pH level indicated a higher initial pH for the WMTA + NaOCl gel group, which equalized after 28 days. SEM analysis initially showed a less homogeneous surface for WMTA + NaOCl gel, but it became similar after 28 days. EDX analysis indicated higher calcium and silicon percentages in the WMTA + NaOCl gel group initially, which increased in both groups after 28 days. Adding 2.25% NaOCl gel to WMTA enhanced odontoblastic integrity in both the short and medium term. In addition, it had a similar chemical composition, surface morphology, and alkalinity when compared to WMTA + DW mixture.
Keywords: Mineral trioxide aggregate; Pulpotomy; Sodium hypochlorite gel